Spinoza's ethics - Spinoza, Benedictus de, 1632-1677 (Princeton University Press, 2020)
"This is a scholarly edition of Eliot's translation of Spinoza's Ethics, which today reads as a fresh, elegant and faithful rendering of the original Latin text. The editor's notes on the text will indicate Eliot's amendments to her manuscript, and discuss those translation decisions which differ from the standard modern English editions, and have a bearing on interpretive and philosophical issues. Eliot's translation of the Ethics is prefaced by an editorial essay which briefly introduces Spinoza's text in its 17th-century context and outlines its key philosophical claims, before discussing Eliot's interest in Spinoza, the circumstances of her translation of the Ethics, and the influence of Spinoza's ideas on her literary work. It presents Eliot's reading of Spinoza in the broader context of the 19th-century reception of his philosophy by Romantic writers, while tracing the distinctive ways in which Eliot drew on Spinoza's radical views on religion, ethics, and human psychology"--